The Level of Individual Biochemical Constants of the Brain of in the Krushinsky-Molodkina Inbred Rat Strain against the Background of Radon Inhalation During Epilepsy - Nikolaishvili, Marina; Nanobashvili, Zakaria; Mitagvaria, Nodar; Chkadua, Gvantsa; Museliani, Tea; Jikia, Gogi; Bilanishvili, Irine; Dondoladze, Khatuna (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: The elucidation of the mechanism of action of radon on antioxidant processes needs further research, however, based on the results of the experiment, it can be concluded that studies on experimental animals have shown that, while inhaling Tskhaltubo water, the phenomenon of hormesis develops. Methods: we placed 10 experimental animals (KM rats) in Radon contained mineral water spa`s sauna. Inhalation of radon-water was administered through the nose, for 10 minutes, once a day, in conditions of high humidity (about 90%) for 10 days. Results: Hormesis regulates oxidative processes in the brain due to the activation of antioxidants expressed in a decrease in existing epileptic seizures and is expressed in the activation of Na / K-ATPase and specific glutaminergic neurons of the "attack center" of the hypothalamus but also with the activation of the entire adaptive-compensatory system. Conclusion: Inhalation of radon contained water can be considered as a method of treatment with an anticonvulsant effect confirmed by experimental studies.